E. Coli Infections Importance of Early Diagnosis and Efficient Treatment - Rodrigo, Luis (IntechOpen, 2020)
Gram-negative Escherichia coli (E. coli) bacteria are the most numerous commensal aerobic germs located in the human colon. Diarrhea caused by E. coli pathogenic strains is a major cause of death in developing countries, especially the sub-Saharan and South Asian areas. Some strains cause diarrhea, and all of them may produce an infectious disease. This book includes ten chapters covering the main aspects of infections related to E. coli, their pathogenic mechanisms, treatments, and resistance to diverse antibiotics.